2013
DOI: 10.5860/crl12-366
|View full text |Cite
|
Sign up to set email alerts
|

Academic Librarians and Research: A Study of Canadian Library Administrator Perspectives

Abstract: Within the literature exploring the role of research in academic librarianship, very little attention has been paid to the perspectives of upper library administrators. This perspective is critical because library administrators play a key role in hiring, evaluating, supporting, promoting, and tenuring professional librarians. As a way of bringing the administrative perspective to these discussions, our study examines how library administrators within the Canadian Association of Research Libraries (CARL) view … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 6 publications
0
20
1
Order By: Relevance
“…The studies that did exist [28,30] differed appreciably from the research attitudes of health sciences librarians described in our study, ranking professional development and promotion and tenure requirements as important motivators, whereas both health sciences academic and hospital librarians in our study ranked demonstration of the value and impact of libraries and provision of guidance as primary motivating factors. The top barrier to research for health sciences librarians was lack of time, nearly universally mentioned as the greatest obstacle in other studies [15,16,28].…”
Section: Institutional Affiliation and Research Productivitycontrasting
confidence: 51%
“…The studies that did exist [28,30] differed appreciably from the research attitudes of health sciences librarians described in our study, ranking professional development and promotion and tenure requirements as important motivators, whereas both health sciences academic and hospital librarians in our study ranked demonstration of the value and impact of libraries and provision of guidance as primary motivating factors. The top barrier to research for health sciences librarians was lack of time, nearly universally mentioned as the greatest obstacle in other studies [15,16,28].…”
Section: Institutional Affiliation and Research Productivitycontrasting
confidence: 51%
“…Henry and Neville reported a lower percentage (63%) having sabbaticals and/or research leave available [5]. Berg, Jacobs, and Cornwall found that 84% of responding library admin istrators provided research leaves and sabbaticals to staff [21], but reiterated Fox [6] in that leaves only count if librarians can take the time to use them.…”
Section: Implications and Future Researchmentioning
confidence: 95%
“…Lack of research skills or confidence in writing abilities are common barriers to research and publication (Berg, Jacobs, & Cornwall, 2013;Koufogiannakis & Crumley, 2006). Research groups and writing groups attempt to provide a forum for collegial exchange of ideas, encouragement, accountability, and feedback (Sapon-White et al, 2004;Stilling, 2012).…”
Section: Literature Reviewmentioning
confidence: 98%